PENGEMBANGAN PRODUKSI MINUMAN RUMPUT LAUT EUCHEMA COOTONII DI DESA TATELI TIGA KECAMATAN MANDOLANG, KABUPATEN MINAHASA - Rarung, Lexy Karel; Kaseger, Berty E. (Universitas Sam Ratulangi, 2018)
AbstractThe target of this program is located in Tateli Tiga Village, Mandolang District, Minahasa Regency, which is geographically very strategic for developing seaweed beverage processing industries. This village is a culinary tourism area, where there are many food and beverage entrepreneurs. North Sulawesi, is a large producer of seaweed, thus the availability of raw materials is easy to obtain and adequate for industrial processing. Processing of seaweed drinks consisting of syrup, juice and instant powder, is very easy and the marketing is not difficult, can be reached by the upper and lower economic class communities. The aim of this program is to develop new business fields to improve the economy of the community and increase the selling value and economy of seaweed. The specific target of this PKM program is 1. producing seaweed drinks to meet sanitary and hygienic requirements, packaged and labeled well / attractively 2. Developing seaweed syrup beverage industry business. The implementation methods agreed with partners are: 1. Problems in the production of seaweed syrup drinks, product marketing and finance 2. Methods for solving problems with counseling, training, mentoring and evaluation. 3 Work procedures for solving problems through surveys, counseling, training, mentoring, evaluation, reporting and journals.Keywords: Euchema cootonii, syrup, processing industry Abstrak Sasaran program ini berlokasi di Desa Tateli Tiga Kecamatan Mandolang Kabupaten Minahasa, yang secara geografi sangat strategis untuk dikembangkan industri pengolahan minuman rumput laut. Desa ini merupakan daerah wisata kuliner, dimana terdapat banyak pengusaha makanan dan minuman. Sulawesi utara, merupakan penghasil rumput laut yang besar, dengan demikian ketersediaan bahan baku mudah diperoleh dan memadai untuk pengolahan secara industri. Pengolahan minuman rumput laut yang terdiri dari sirup, sari dan serbuk instant, sangat mudah serta pemasarannya tidak sukar, dapat dijangkau oleh masyarakat kelas ekonomi atas maupun bawah. Tujuan program ini yaitu pengembangan lapangan usaha baru untuk meningkatkatkan ekonomi masyarakat serta meningkatkan nilai jual dan ekonomi rumput laut. Target khusus program PKM ini yaitu 1. memproduksi minuman rumput laut memenuhi syarat sanitasi dan higienis, dikemas dan dilabel dengan baik/menarik 2. Mengembangkan usaha industri minuman sirup rumput laut . Adapun metoda pelaksanaan yang disepakati dengan mitra yaitu: 1. Masalah produksi minuman sirup rumput laut, pemasaran produk dan keuangan 2. Metoda untuk menyelesaikan masalah dengan penyuluhan, pelatihan, pendampingan dan evaluasi. 3 Prosedur kerja untuk menyelesaikan masalah melalui survey, penyuluhan, pelatihan, pendampingan, evalusi, pelaporan dan jurnal.Kata kunci: Euchema cootonii, sirup, industri pengolahan